Effect of Using Combined Square Nozzle & winglet with Helical Tape on Thermal Characteristics in Tube Heat Exchanger - Hoshi, Hisham Assi; Ahmed, Israa S.; Abdulmunem, Abdulmunem R. (Al-Khwarizmi Engineering Journal, 2018)
Influence of combined square nozzle with helical tape inserted in a constant heat flux tube on heat transfer enhancement for turbulent airflow for Reynolds number ranging from 7000 to 14500 were investigated experimentally. Three different pitch ratios for square nozzle (PR = 5.8, 7.7 and 11.6) according to three different numbers of square nozzle (N = 3, 4 and 5) and constant pitch ratios for helical tape were used. The results observed that the Nusselt number and friction factor for combination with winglets were found to be up to 33.8 % and 21.4 %, respectively higher than nozzle alone for pitch ratio PR=5.8. The maximum value of thermal performance for using combination with winglets was about 1.351 for pitch ratio= 5.8. Nusselt number and friction factor correlations from experimental data were developed for turbulent flow.